Foreign Direct Invesment Flows in OIC Country - Nida Laili Fitriyah; Alvira Aina A'yun; Khofidlotur Rofi’ah; Sri Herianingrum (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
Investment is one of the funding needed by all countries to develop manufacturing and the economy. This study aims to examine the factors affecting the foreign direct investment flow among OIC countries. In order to achieve the goal, the authors use quantitative research methods using a regression test of data panels on the secondary data that has been collected. Panel data for the period 2012-2018 are used. The results showed that inflation and political stability have a significant and positive impact on FDI's entry. Meanwhile, corruption variables have a negative not significant effect on FDI and economic growth variables have a positive effect but not significant in FDI’s entry in OIC Country. This research examines simultaneously the factors that determine FDI flow in OIC Country. This Paper provides value for policymakers in OIC Country recognized the need for outside capital as one of fund for the public. As well as consider the investor takes the decision in investing his funds especially in Asian countries member of Islamic Cooperation (OIC).